Process for modeling competencies for developing serious games - Arturo Barajas Saavedra; Francisco Javier Álvarez Rodríguez; Jaime Muñoz Arteaga; Ana Cecilia Oviedo de Luna (Revista Electrónica de Investigación Educativa)
Nowadays, serious games play an outstanding role in the adoption of competencies since they provide immersion, fun, motivation and a high level of engagement among users. This research proposes a process called “Competency-based Decomposition” that allows the identification and modelling of syllabus competencies for the development of serious games to ensure the correct implementation of pedagogical aspects. This is extremely important to ensure a high level of adoption of the competencies by game users. The focus of this research is to guarantee the correct implementation of pedagogical aspects (learning activities and content, expected learning, etc.) in the production of serious games. This article presents the theoretical foundations of the research and details of the competency-based decomposition process, including the application process and its application in mathematics classes for the sixth grade of elementary school. The results obtained in this research are the successful identification of six competencies and 19 areas of knowledge, and the production of 50 short serious games based on the identified competencies and areas of knowledge. These games have been tested on students, resulting in an improvement in learning.